In a post-Hegelian spirit - Dorrien, Gary J.,Hegel, Georg Wilhelm Friedrich (Baylor University Press, 2020)
Hegel broke open the deadliest assumptions of Western thought by conceiving being as becoming and consciousness as the social-subjective relation of spirit to itself, yet his white Eurocentric conceits were grotesquely inflated even by the standards of his time. With In a Post-Hegelian Spirit , Gary Dorrien emphasizes both sides of this Hegelian legacy, contending that it takes a great deal of digging and refuting to recover the parts of Hegel that still matter for religious thought. By distilling his signature argument about the role of post-Kantian idealism in modern Christian thought, Dorrien fashions a liberationist form of religious idealism: a post-Hegelian religious philosophy that is simultaneously both Hegelian as it expounds a fluid, holistic, open, intersubjective, ambiguous, tragic, and reconciliatory idea of revelation and post-Hegelian, as it rejects the deep-seated flaws in Hegel's thought. Dorrien mines Kant, Schleiermacher, and Hegel as the foundation of his argument about intellectual intuition and the creative power of subjectivity. After analyzing critiques of Hegel by SA,ren Kierkegaard, Karl Marx, Karl Barth, and Emmanuel Levinas, Dorrien contends that though these monumental figures were penetrating in their assessments, they appear one-sided compared to Hegel. In a Post-Hegelian Spirit further engages with the personal idealist tradition founded by Borden Parker Bowne, the process tradition founded by Alfred North Whitehead, and the daring cultural contributions of Paul Tillich, W. E. B. Du Bois, Martin Luther King, Jr., Rosemary Radford Ruether, David Tracy, Peter Hodgson, Edward Farley, Catherine Keller, and Monica Coleman
Literaturangaben
Keywords: Hegel; Georg Wilhelm Friedrich; Philosophical theology